2017
DOI: 10.1111/pedi.12573
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric diabetes training for healthcare professionals in Europe: Time for change

Abstract: There is a severe shortage of high quality, standardized training for HCPs across the majority of European countries. Lack of trained HCPs for CYP with diabetes will result in the delivery of suboptimal care and impact on health, wellbeing and clinical and psychological outcomes. The EU-CDEC template can be used to increase access to high quality training provision for all HCPs across Europe and worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The reports of the Dose Adjustment for Normal Eating (DAFNE) study emphasised the positive effect of CC on the quality of life [ 58 ]. So far, many kinds of structural education programs for T1D have been reported [ 59 , 60 ]. Most of these programs included CC and showed the improvement of patients’ adherence, as well as motivation.…”
Section: Insulin-to-carb Ratio (Icr) Insulin Sensitivity Factor (mentioning
confidence: 99%
See 1 more Smart Citation
“…The reports of the Dose Adjustment for Normal Eating (DAFNE) study emphasised the positive effect of CC on the quality of life [ 58 ]. So far, many kinds of structural education programs for T1D have been reported [ 59 , 60 ]. Most of these programs included CC and showed the improvement of patients’ adherence, as well as motivation.…”
Section: Insulin-to-carb Ratio (Icr) Insulin Sensitivity Factor (mentioning
confidence: 99%
“…Therefore, CC has a positive effect on patients’ adherence and motivation too. In addition, it has been observed that CC also has a positive effect on the parents and caregivers, who are the key persons for the treatment of infants and young children with T1D [ 59 , 60 ].…”
Section: Insulin-to-carb Ratio (Icr) Insulin Sensitivity Factor (mentioning
confidence: 99%
“…The intestinal bacterial imbalance (dysbiosis) and the enteropathogenic parasites that affect the gut barrier, have been independently associated with increased risk of developing T1D or CD in genetically predisposed children [ 9 , 23 , 35 ]. However, there is no information regarding the effect of enteropathogenic parasites’ infections on bacterial dysbiosis or vice versa, in children developing autoimmunity.…”
Section: Introductionmentioning
confidence: 99%
“…Especially considering that diabetes care is unequal worldwide, these Schools could play a major role as a diabetes care and research training program for early-career physicians and healthcare professionals. [2][3][4][5] Therefore, we designed retrospective qualitative surveys to evaluate the perceived impact of the ISSPs and ISSHPs on aspects related to participants' career development, scientific skills, and networking over the last 20-and 16-years, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of the impact of both courses on professionals' career in diabetes care and research holds particular interest for the validation and future of both Schools. Especially considering that diabetes care is unequal worldwide, these Schools could play a major role as a diabetes care and research training program for early‐career physicians and healthcare professionals 2–5 …”
Section: Introductionmentioning
confidence: 99%